Human Ventricular Unloading Induces Cardiomyocyte Proliferation - Canseco, Diana C.; Kimura, Wataru; Garg, Sonia; Mukherjee, Shibani; Bhattacharya, Souparno; Abdisalaam, Salim; Das, Sandeep; Asaithamby, Aroumougame; Mammen, Pradeep P.A.; Sadek, Hesham A. (Journal of the American College of Cardiology, 2015)
The adult mammalian heart is incapable of meaningful regeneration after substantial cardiomyocyte loss, primarily due to the inability of adult cardiomyocytes to divide. Our group recently showed that mitochondria-mediated oxidative DNA damage is an important regulator of postnatal cardiomyocyte cell cycle arrest. However, it is not known whether mechanical load also plays a role in this process. We reasoned that the postnatal physiological increase in mechanical load contributes to the increase in mitochondrial content, with subsequent activation of DNA damage response (DDR) and permanent cell cycle arrest of cardiomyocytes. The purpose of this study was to test the effect of mechanical unloading on mitochondrial mass, DDR, and cardiomyocyte proliferation. We examined the effect of human ventricular unloading after implantation of left ventricular assist devices (LVADs) on mitochondrial content, DDR, and cardiomyocyte proliferation in 10 matched left ventricular samples collected at the time of LVAD implantation (pre-LVAD) and at the time of explantation (post-LVAD). We found that post-LVAD hearts showed up to a 60% decrease in mitochondrial content and up to a 45% decrease in cardiomyocyte size compared with pre-LVAD hearts. Moreover, we quantified cardiomyocyte nuclear foci of phosphorylated ataxia telangiectasia mutated protein, an upstream regulator of the DDR pathway, and we found a significant decrease in the number of nuclear phosphorylated ataxia telangiectasia mutated foci in the post-LVAD hearts. Finally, we examined cardiomyocyte mitosis and cytokinesis and found a statistically significant increase in both phosphorylated histone H3–positive, and Aurora B–positive cardiomyocytes in the post-LVAD hearts. Importantly, these results were driven by statistical significance in hearts exposed to longer durations of mechanical unloading. Prolonged mechanical unloading induces adult human cardiomyocyte proliferation, possibly through prevention of mitochondria-mediated activation of DDR.